2022
DOI: 10.1177/10659129221087264
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Confusion: Ideological Labels in China

Abstract: The idea of a left-right ideological dimension helps citizens and parties organize their thinking about politics. While the left-right dimension is traditionally organized around questions of inequality and change in democracies, its meaning under authoritarian rule remains uncertain. This paper uses two national surveys to investigate the policy, partisan, and symbolic content of the left-right dimension in China. The analysis of these surveys reveals that while many Chinese citizens are willing to locate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Thus, the two coexistent mechanisms complicate the relationship between RWA and SDO in China, potentially working in opposite directions. This can also explain why social attitudes are less ‘constrained’ to a one‐dimensional ideological spectrum in China compared to North America and Europe (Pan & Xu, 2018; Wu, 2023). Nevertheless, whether there can be two opposite mechanisms is a question that needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the two coexistent mechanisms complicate the relationship between RWA and SDO in China, potentially working in opposite directions. This can also explain why social attitudes are less ‘constrained’ to a one‐dimensional ideological spectrum in China compared to North America and Europe (Pan & Xu, 2018; Wu, 2023). Nevertheless, whether there can be two opposite mechanisms is a question that needs to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision was made deliberately. Specifically in the context of China, the conventional self‐identified measurement of ideology has been criticized for the lack of a collectively shared understanding of the left‐right labels (Ma & Lewis, 2020; Wu, 2023). By trial and error, we included an item of self‐identified ideology in our survey, whose results are shown in the Appendix S1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations